2012
DOI: 10.3382/ps.2011-01893
|View full text |Cite
|
Sign up to set email alerts
|

Phytate and other nutrient components of feed ingredients for poultry

Abstract: Samples of feed ingredients were collected from poultry feed mills in the United States and Canada: corn (133), soybean meal (114), corn distillers dried grains with solubles (DDGS; 89), bakery by-product meal (95), wheat (22), wheat middlings (31), canola meal (21), and wheat shorts (15). The samples were assayed by standard wet chemical techniques for CP, fat, neutral detergent fiber (NDF), acid detergent fiber, calcium, phosphorus, phytate phosphorus, and ash. There was considerable variation found in most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 21 publications
5
25
2
3
Order By: Relevance
“…The phytic acid concentration in corn distillers' grains with solubles has been reported to be 0.257% in a prior investigation [29]. In this study, the phytic acid content of the corn distillers' grains with solubles was found to range from 0.220% to 0.255% which is very similar to the value determined in the previous study [29].…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The phytic acid concentration in corn distillers' grains with solubles has been reported to be 0.257% in a prior investigation [29]. In this study, the phytic acid content of the corn distillers' grains with solubles was found to range from 0.220% to 0.255% which is very similar to the value determined in the previous study [29].…”
Section: Resultssupporting
confidence: 79%
“…In this study, the phytic acid content of the corn distillers' grains with solubles was found to range from 0.220% to 0.255% which is very similar to the value determined in the previous study [29]. Initially, the effect of treating the grains with solubles with 2 or 4 units of fungal phytase activity per g of grains with solubles was explored relative to temperature and compared to untreated samples of corn distillers' grains with solubles.…”
Section: Resultsmentioning
confidence: 58%
“…The differences in results between fish meal and soybean meal is assumably due to the presence of phytate component such as oligosaccharide and anti-trypsin in soybean meal. The inferior results found for soybean meal was seemingly attributable to the presence of phytate compound (Banaszkiewicz, 2011;Tahir et al, 2012), non-protein soluble component such as oligosaccharide (Kocher et al, 2002;Oliveira and Stein, 2016), and trypsin inhibitor (Banaszkiewicz, 2011;Pacheco et al, 2013). Phytate compound in soybean meal has been reported to be varied with the range of betwen 1 and 1.5% (Banaszkiewicz, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Bahan pakan berasal dari hasil samping proses penggilingan biji-bijian tanaman serealia, termasuk pula bungkil, dilaporkan mengandung asam fitat lebih tinggi dibandingkan dengan biji legum (Steiner et al 2007). Tahir et al (2012) melaporkan bahwa kandungan asam fitat dalam beberapa bahan pakan yang sering digunakan sebagai bahan pakan penyusun ransum unggas adalah sebagai berikut, jagung (0,186%), bungkil kedelai (0,395%), distiller's dried grains with solubles (DDGS) (0,257%), tepung limbah roti (0,192%), gandum (0,251%) dan tepung kanola (0,695%). Dedak padi termasuk bahan pakan yang mengandung asam fitat tinggi.…”
Section: Gambar 1 Struktur Kimia Asam Fitatunclassified